Method for determining the margin of stability of the cascades of the d-18t engine compressor in transient modes - Кулик, М. С.; Панін, В. В.; Кінащук, І. Ф. (Proceedings of National Aviation University (archive), 2021)
The method of determining the stability margins of the compressor stages of aircraft long-term gas turbine engines in transient modes of operation according to the objective means of control is considered. The results of approbation of this method on the example of the D-18T engine are given.